2011
DOI: 10.1007/s12015-011-9234-x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Extremity Ischemia Augments CD34+ Progenitor Cell Availability

Abstract: Peripheral blood is an easily accessed source for stem cell production; however, the number of cells produced is relatively low. We hypothesized that ischemic preconditioning may serve as a safe method to increase the number of CD34+ cells that can be harvested and cultured in a short period. This study was conducted to test this hypothesis by examining the safety and efficacy of brief, transient ischemia of the lower limbs to augment the number of cells that can be produced from blood of healthy volunteers. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Others have found, however, that RLIC did not affect serum levels of tissue plasminogen activator (tPA), nor tPA inhibitor antigen and activity, in healthy humans (Pedersen et al, 2012). For VEGF, one study found that RLIC increased plasma VEGF levels and the number of circulating endothelial progenitor cells (Kimura et al, 2007), while another reported that VEGF concentrations did not change 0.5, 12, or 24 hours after conditioning (Czeiger et al, 2011), in healthy adults. Regarding inflammatory biomarkers, RLIC altered levels of IL-6 and TNF-α in infants undergoing cardiac surgery (Zhou et al, 2010), but caused no change in IL-6 or TNF-α levels in children undergoing surgery for a congenital heart defect (Cheung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Others have found, however, that RLIC did not affect serum levels of tissue plasminogen activator (tPA), nor tPA inhibitor antigen and activity, in healthy humans (Pedersen et al, 2012). For VEGF, one study found that RLIC increased plasma VEGF levels and the number of circulating endothelial progenitor cells (Kimura et al, 2007), while another reported that VEGF concentrations did not change 0.5, 12, or 24 hours after conditioning (Czeiger et al, 2011), in healthy adults. Regarding inflammatory biomarkers, RLIC altered levels of IL-6 and TNF-α in infants undergoing cardiac surgery (Zhou et al, 2010), but caused no change in IL-6 or TNF-α levels in children undergoing surgery for a congenital heart defect (Cheung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that EPC mobilisation occurs following RIPC in both mice and humans [82, 83], and this appears likely to contribute significantly to the late phase cardioprotective effects of RIPC [82]. We therefore hypothesise that this may be another important and under-recognised mechanism behind the poorer response to RIPC in T2DM, particularly in the rarely-studied late phase of protection.…”
Section: Difficulties In Clinical Translation Of Ischaemic Conditionimentioning
confidence: 91%
“…It is felt the mechanisms are similar, but that both the early and late phase of RIPC are reliant on neural pathways to a greater degree than local ischaemic preconditioning [42]. The late phase of RIPC has also been shown to result in the mobilisation of bone marrow-derived stem cells, including CD34+ cells, into both the peripheral blood and damaged myocardium, which have the capacity to induce angiogenesis and endothelial repair [82, 83]. …”
Section: Remote Ischaemic Conditioning Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations